2016
DOI: 10.18639/onbt.2016.03.1257
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes tumor of the breast: Wolf inside the sheep’s skin!

Abstract: Phyllodes tumor, previously known as cystosarcoma phyllodes, is a rare fibro-epithelial tumor of breast constituting <1% of all the breast tumors. It is classified into benign, borderline, and malignant subtypes depending upon the histological criteria defined by the World Health Organization and also has an independent prognostic significance. Accurate pretreatment histological diagnosis is important for the optimal management of phyllodes tumor so that low recurrence rates, improved survival, and optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In our case, the situation of the apparent mammary abscess misled doctors and surgical drainage was performed. However, in presence of a defined lump in the left breast, a US-guided core biopsy is the appropriate approach to reveal the presence of a biphasic lesion [ 20 ]. With that result, a surgical excision of the entire lump and a small normal tissue margin instead of a surgical drainage with an open biopsy of the mass is recommended [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the situation of the apparent mammary abscess misled doctors and surgical drainage was performed. However, in presence of a defined lump in the left breast, a US-guided core biopsy is the appropriate approach to reveal the presence of a biphasic lesion [ 20 ]. With that result, a surgical excision of the entire lump and a small normal tissue margin instead of a surgical drainage with an open biopsy of the mass is recommended [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Additionally, data from the Korean group also suggested that there was no survival benefit over 7 years with IMLN-RT. 8 9 With no evidence of overall survival benefit and toxicity concerns (pulmonary and cardiac fibrosis), the adoption of pIMLN-RT in routine clinical practice has been variable. Newer techniques of therapeutic RT with three-dimensional conformal radiotherapy (3DCRT), intensity-modulated RT (IMRT), volume modulated arc therapy (VMAT), and proton therapy compared to the conventional two-dimensional technique have partially abrogated the concerns of toxicity.…”
Section: Introductionmentioning
confidence: 99%